Evidence for dissociation between the perceptual and visuomotor systems in humans. - Yamagishi, N. (2001)
When a visual stimulus is continuously moved behind a small stationary window, the window appears displaced in the direction of motion of the stimulus. In this study we showed that the magnitude of this illusion is dependent on (i) whether a perceptual or visuomotor task is used for judging the location of the window (ii) the directional signature of the stimulus, and (iii) whether or not there is a significant delay between the end of the visual presentation and the initiation of the localization measure. Our stimulus was a drifting sinusoidal grating windowed in space by a stationary, two-dimensional, Gaussian envelope (sigma=1 cycle of sinusoid). Localization measures were made following either a short (200 ms) or long (4.2 s) post-stimulus delay. The visuomotor localization error was up to three times greater than the perceptual error for a short delay. However, the visuomotor and perceptual localization measures were similar for a long delay. Our results provide evidence in support of the hypothesis that separate cortical pathways exist for visual perception and visually guided action and that delayed actions rely on stored perceptual information.